A Problem-Based Learning Model to Improve English Learning Outcomes: A Study in Middle-School Students - Sukaesih, Cici; Fatmasari, Elly; Iskandar, Iskandar (ETDC: Indonesian Journal of Research and Educational Review, 2023)
Teaching is not just a matter of telling. Learning is not an automatic consequence of contemplating information in the minds of students. Learning requires mental involvement and students' work. Explanation and demonstration alone will not produce lasting learning outcomes. Which can produce learning outcomes, including the activities of contextual learning methods with problem-based learning teaching models. The source of the data for this research is the seventh-grade students of SMPN 1 Sidomulyo Odd Semester for the 2020/2021 academic year, totaling 34 students consisting of 13 male students and 21 female students. The data collected are quantitative and qualitative. Quantitative data is data obtained from formative tests in each cycle. While qualitative in the form of observations in each learning cycle, the data obtained is then converted into success criteria to determine whether student learning outcomes can be seen and how they improve. This study uses two cycles of action research. Each round consists of four stages, namely: design, observation activities, and reflection. From the data obtained in the form of formative test results and observation sheets of teaching and learning activities, it was found that student learning achievement has increased from cycle one to cycle two. In the first cycle, student learning outcomes in the very good category were 29.41%, and in the second cycle, the learning outcomes in the very good category increased to 70.59%. This study concludes that the problem-based learning (PBL) learning model can have a positive effect on the learning outcomes of class VII F students at SMP 1 Sidomulyo, and this learning model can be used as an alternative to learning English.